Analisis Spektrum Energi dan Fungsi Gelombang Potensial Non-Central Menggunakan Supersimetri Mekanika Kuantum - Saregar, Antomi (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2015)
The objectives of this study were: 1) to describe the results of wave and energy function of the Non-central potential system of potential combinations of trigonometric Poschl-Teller plus Rosen Morse, Coloumb and OH 3D potential, and Rosen Morse trigonometric potential plus Pochl-Teller analyzed using Supersymmetry quantum mechanics (SUSY QM); 2) to know the visualization of wave function and energy level at point 1. This study is a literature study conducted from July 2013 to December 2015. Non-central potential of potential combinations of trigonometric Poschl-Teller potency plus Rosen Morse, Coloumb and OH 3D potential and potential Rosen Morse trigonometry plus Pochl-Teller is a potential that has a shape invariance properties. Recent developments, the SUSY method has been successfully used to create complete and precise mathematical analysis of the resolution of some non-central potentials in a closed system. By applying a lowering operator to a basic level wave function, a basic level wave function is obtained, while a top-level wave function is obtained by using a rising operator operated at a ground-level wave function and so on. While the value of energy in a closed system obtained by using the nature of the invariant shape. Tujuan Penelitian ini adalah: 1) mendeskripsikan hasil fungsi gelombang dan energi dari sistem potensial Non sentral hasil kombinasi potensial Poschl-Teller trigonometri plus potensial Rosen Morse, Coloumb, dan OH 3D, serta potensial Rosen Morse trigonometri plus Pochl-Teller yang dianalisis menggunakan metode Supersymmetry mekanika kuantum (SUSY QM); 2) mengetahui visualisasidari fungsi gelombangdan tingkat energy pada poin 1. Penelitian ini merupakan studi literatur yang dilakukan mulai bulan Juli 2013 s.d. Desember 2015. Potensial non sentral hasil kombinasi potensial Poschl-Teller trigonometri plus potensial Rosen Morse, Coloumb, dan OH 3D serta potensial Rosen Morse trigonometri plus Pochl-Teller merupakan potensial yang mempunyai sifat shape invariance.Perkembangan terakhir, metode SUSY telah berhasil digunakan untuk membuat analisis matematis secara lengkap dan tepat penyelesaian beberapa potensial non sentral dalam sistem tertutup. Dengan mengaplikasikan operator penurun pada fungsi gelombang tingkat dasar diperoleh fungsi gelombang tingkat dasar, sedangkan fungsi gelombang tingkat atas satu diperoleh dengan menggunakan operator penaik yang dioperasikan pada fungsi gelombang tingkat dasar dan seterusnya. Sedangkan nilai energinya dalam sistem tertutup diperoleh dengan menggunakan sifat shape invariant.